-4w-26=3(w+3)

Simple and best practice solution for -4w-26=3(w+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4w-26=3(w+3) equation:



-4w-26=3(w+3)
We move all terms to the left:
-4w-26-(3(w+3))=0
We calculate terms in parentheses: -(3(w+3)), so:
3(w+3)
We multiply parentheses
3w+9
Back to the equation:
-(3w+9)
We get rid of parentheses
-4w-3w-9-26=0
We add all the numbers together, and all the variables
-7w-35=0
We move all terms containing w to the left, all other terms to the right
-7w=35
w=35/-7
w=-5

See similar equations:

| x2-11x+5=0 | | 4(5z-1)-2(z+2)=7(z+1) | | 4y − 17 = 35 | | 5x-2/4=10 | | x+x+x+0.5x-35-46=360 | | 2(y-1)=7y+5-2(-5y-1) | | 14y-5=35 | | -g+12=19 | | (y+5)/(10)=(7)/(8) | | -13.8=-2.6+w/6 | | 1/3x+1/5=7/6(-3x+5) | | -7-3y=18 | | ½p+2=11 | | -7-y3=19 | | 25=10y+825=10y+8 | | 1-p=11-10 | | -2x+7=-21-2x+7=-21 | | 4−|5−2x|=9 | | (x-5)(-3+7)-(x-5)=0 | | d-5/9=3/9 | | −1.5|x+3|=−7.5 | | 9w+33=12w-279w+33=12w-27 | | −1.5|x+3|=−7.5. | | 3y2+15y=0 | | 9w+33=12w-279w+33=12w-21 | | -7.78+2.6d=4.1d+4.82 | | 40-24=16x | | 4n+15+5n+20=180 | | 9x+42=6x+30 | | 5=3x+2=11 | | 10x+4-8x=2(-1) | | 1/3x-8=5x+6 |

Equations solver categories